2015
DOI: 10.1177/1534734615593190
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c and Lower Extremity Amputation Risk in Patients With Diabetes

Abstract: In this meta-analysis, we aimed to assess glycosylated hemoglobin (HbA1c) level and lower extremity amputation (LEA) risk in patients with diabetes. Systematic computerized searches of the PubMed and Web of Knowledge were performed. We compared HbA1c level between groups with LEA and without LEA by meta-analysis; we also examined the dose-response relationship between HbA1c level and LEA risk. Sixteen studies were included in the meta-analysis. Eleven studies with 43,566 patients compared HbA1c between groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 32 publications
5
37
0
1
Order By: Relevance
“…Although there were inconsistencies among studies regarding risk factors, HbA1c elevation was found to be closely associated with increased risk of amputation in different reports . In our analysis, elevated HbA1c levels also led to a significantly higher rate of amputations (OR 1.317), which was compatible with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Although there were inconsistencies among studies regarding risk factors, HbA1c elevation was found to be closely associated with increased risk of amputation in different reports . In our analysis, elevated HbA1c levels also led to a significantly higher rate of amputations (OR 1.317), which was compatible with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…Matthews et al demonstrate this in Table 3 in their paper [10] by estimating the number of amputations in subgroups that did not have independent risk factors for amputation identified in CANVAS and CANVAS-R, including male sex, non-Asian ethnicity, prior amputation, peripheral vascular (probably artery) disease, neuropathy, albuminuria and poorer glucose control. These risk factors for amputation are largely consistent with prior reports [2][3][4][5][6][7][8], as mentioned earlier in this commentary.…”
Section: The Design Of Canvas and Canvas-r And Implications For Clinisupporting
confidence: 91%
“…Diabetic foot ulcers usually occur due to a direct or indirect trauma associated with loss of protective sensation and are frequently accompanied by peripheral artery disease. Several factors increase the risk of LEA in diabetic individuals with or without diabetic foot ulcers, such as male sex, sensory neuropathy, peripheral artery disease, prior history of foot ulcer or amputation, poor glycaemic control, renal dysfunction, non-Asian ethnicity and presence of infection [2][3][4][5][6][7][8]. Recently, the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial, in which individuals were randomised to receive intensive therapy (HbA 1c <42 mmol/mol [<6%]) or standard glycaemic control (HbA 1c 53-63 mmol/mol [7.0-7.9%]), showed that the intensive regimen resulted in a significant decrease in LEA risk and that mean HbA 1c strongly predicted LEA occurrence [9].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Optimal glycaemic control is associated with reduced risk of lower extremity amputation and other microvascular events, and is the cornerstone of diabetes therapy. 8,9 Sodium glucose co-transporter 2 (SGLT2) inhibitors reduce plasma glucose by increasing the renal threshold for glucose, leading to increased urinary glucose excretion and a mild osmotic diuresis that may be associated with a reduction in intravascular volume. 10,11 Canagliflozin, dapagliflozin and empagliflozin are SGLT2 inhibitors approved for the treatment of T2DM in the USA.…”
mentioning
confidence: 99%